2011
DOI: 10.1002/ptr.3268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taspine on proliferation and apoptosis by regulating caspase‐3 expression and the ratio of Bax/Bcl‐2 in A431 cells

Abstract: Taspine is an active component isolated from Radix et Rhizoma Leonticis. It has been shown that taspine can inhibit tumour angiogenesis. However, how it inhibits the proliferation of, and induces apoptosis in, A431 cells is unknown. The study investigated the effects of taspine on the proliferation and apoptosis in the A431 cell line using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), flow cytometry, transmission electron microscopy (TEM), western blotting (WB) and real-time reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…The Bcl-2 family plays an important role in the regulation of cell apoptosis (Kang and Reynolds, 2009;Zhou et al, 2011). When levels of anti-apoptotic proteins on the mitochondrial membrane, such as Bcl-2, Bcl-xL, and Mcl-1 decrease and levels of pro-apoptotic proteins increase or remain unchanged, the ratio of Bcl-2/Bax, Bcl-xL/Bax, and Mcl-1/Bax decreases, leading to a relative increase in Bax (Zhang et al, 2011). Bax proteins change their configuration to form oligomers and insert into mitochondrial membrane as pores (Tait and Green, 2010), which leads to the release of cytochrome c from mitochondria and the initiation of the caspase pathway of apoptosis (Fan et al, 2007;Adams and Cory, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The Bcl-2 family plays an important role in the regulation of cell apoptosis (Kang and Reynolds, 2009;Zhou et al, 2011). When levels of anti-apoptotic proteins on the mitochondrial membrane, such as Bcl-2, Bcl-xL, and Mcl-1 decrease and levels of pro-apoptotic proteins increase or remain unchanged, the ratio of Bcl-2/Bax, Bcl-xL/Bax, and Mcl-1/Bax decreases, leading to a relative increase in Bax (Zhang et al, 2011). Bax proteins change their configuration to form oligomers and insert into mitochondrial membrane as pores (Tait and Green, 2010), which leads to the release of cytochrome c from mitochondria and the initiation of the caspase pathway of apoptosis (Fan et al, 2007;Adams and Cory, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Taspine has an inhibitory effect on growth of HUVECs and can induce its apoptosis by decreasing Bcl-2 expression and increasing bax expression. Zhang et al continuously investigated the effects of taspine on the proliferation and apoptosis in the A431 cell [60]. The cell cycle was significantly stopped at S phase, and nuclear karyopyknosis, chromatin agglutination, and typical apoptotic bodies were found after taspine treatment in A431 cells.…”
Section: Bioactivitymentioning
confidence: 99%
“…The caspase family is responsible for the execution phase of apoptosis [30], and caspase-3 plays a central role in this process. Once activated, caspase-3 rapidly induces the cleavage of poly ADP-ribose polymerase (PARP) and forms cleaved caspase-3, which in turn leads to the degradation of DNA into nucleosomal fragments [31]. Our results showed that CpG-ODN treatment led to a low level of caspase-3 expression and the disappearance of cleaved caspase-3 after irradiation, suggesting that caspase-3 activation was inhibited.…”
Section: Discussionmentioning
confidence: 84%